2009
DOI: 10.1371/journal.pntd.0000492
|View full text |Cite
|
Sign up to set email alerts
|

Trachoma in Western Equatoria State, Southern Sudan: Implications for National Control

Abstract: BackgroundTrachoma is thought to be common over large parts of Southern Sudan. However, many areas of the country, particularly west of the Nile, have not yet been surveyed. The aim of this study was to confirm whether trachoma extends into Western Equatoria State from neighboring Central Equatoria, where trachoma is highly prevalent, and whether intervention with the SAFE strategy is required.Methods and FindingsPopulation-based cross-sectional surveys were conducted using a two-stage cluster random sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…These findings indicate that trachoma constitutes a major problem to public health in Southern Sudan [27] . However, not all of Southern Sudan is equally at risk, as indicated by recent surveys that identified areas where trachoma is not endemic [28] . Generating a better understanding of the geographical distribution of trachoma is therefore important so that the limited available resources can be better targeted.…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate that trachoma constitutes a major problem to public health in Southern Sudan [27] . However, not all of Southern Sudan is equally at risk, as indicated by recent surveys that identified areas where trachoma is not endemic [28] . Generating a better understanding of the geographical distribution of trachoma is therefore important so that the limited available resources can be better targeted.…”
Section: Introductionmentioning
confidence: 99%
“…Trachoma surveys have also been undertaken in a number of areas in the country [6][8]. For LF, schistosomiasis and STH, by contrast, systematic prevalence data are not available, with previous studies in Southern Sudan having been few and limited in scale [9]–[11].…”
Section: Introductionmentioning
confidence: 99%
“…In Southern Sudan, up until now, the distribution of onchocerciasis has been comprehensively mapped by the Ministry of Health, Government of Southern Sudan (MoH-GoSS) with assistance from the African Program for Onchocerciasis Control [5] . Trachoma surveys have also been undertaken in a number of areas in the country [6] [8] . For LF, schistosomiasis and STH, by contrast, systematic prevalence data are not available, with previous studies in Southern Sudan having been few and limited in scale [9] – [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous baseline and impact surveys showed that the prevalence of trachoma varied throughout the country, with low levels of trachoma detected in Western Equatoria [ 5 ], Northern Bahr-el-Ghazal [ 6 ], and Central [ 18 ] states. Hyper endemic levels of trachoma were detected in the Greater Upper Nile region of Jonglei, Upper Nile, and Unity states [ 3 , 7 ], and Eastern Equatoria state [ 3 ].…”
Section: Discussionmentioning
confidence: 99%